Pain: Friend or Foe? A Neurobiologic Perspective: The 2008 Bonica Award Lecture. Issue 6 (1st October 2009) - Cervero, Fernando
Abstract : Pain is a protective sensation, but it can also be a burden without any useful value. Pain as a friend warns of impending damage and protects the body from injury. Pain as a foe is a useless sensation that makes the underlying problem worse and becomes a disease in its own right. Mechanistically, the systems that mediate good pain and bad pain are often the same, with bad pain being the result of such mechanisms being triggered inappropriately, by irrelevant stimuli or with a time course and intensity disproportionate to the originating cause. We are beginning to know more about the neurobiology of bad pain. The relevant mechanisms are often linked to dysfunction or disease of the nervous system, either of the peripheral nerves or of the central nervous system itself. For example, under normal conditions, activity in large, myelinated Aβ-fibers inhibits nociceptive primary afferent inputs to the central nervous system. However, in inflammatory and neuropathic conditions, these actions are reversed, leading to touch-evoked pain or tactile allodynia. The mechanism responsible for this reversal is a change in the synaptic actions of γ-aminobutyric acid that switches from being an inhibitory neurotransmitter to an excitatory one. Our challenge was to devise methods for pain relief based on elimination of the useless aspects of pain and the restoration of the protective qualities of normal pain sensation.